Large eddy simulation of buoyancy-driven natural ventilation-twin-plume flow - Faisal Durrani; Malcolm Cook; Jim McGuirk; N.B. Kaye (2013)
This paper presents results of a Large Eddy Simulation (LES) of buoyancy-driven natural ventilation in which two unequal heat sources are used to drive the flow. The aim of this work was to assess the performance of LES in modelling turbulent thermal plumes in a naturally ventilated enclosure and to analyse their interaction with each other. The sub-grid scales of the flow have been resolved by using the Smagorinsky sub-grid scale model. It was found that LES results for the interface height agree well with the theoretical predictions of Linden and Kaye (2006). However, instead of a step change in temperature, as suggested by theory, there exists a more diffuse interface. The merging height of the two plumes and the volume flow rates in the far field merged plume agreed closely with theoretical predictions. Analysis of the pressure isosurfaces demonstrated the interaction phenomena of the two plumes, the coherent structures and the behaviour of the interface.